INVENTARISASI GULMA PADA TEGAKAN TANAMAN MUDA Eucalyptus spp. (Weed Inventory on stand of young Eucalyptus spp.) - Rahmat Faisal; Edi Batara Mulya Siregar; Nelly Anna (Peronema Forestry Science Journal, 2013)
Eucalyptus spp is a fast-growing plant species that have economic value and multifunction primarily developed as a raw material for the pulp extensively. Weeds is one factor that can inhibit the growth of Eucalyptus spp.This study aims to inventory the types of weeds present in young Eucalyptus spp. and know the composition and dominance of the types of weeds that were needed in the management of industrial plantations of Eucalyptus spp. The research was conducted at PT. Toba Pulp Lestari, Tbk Aek Nauli sector in March-June 2011. The results showed that the diversity of weed found in Eucalyptus spp plantation consisted of 15 families and 39 species were relatively similar and were dominated by the family Rubiaceae, Asteraceae, Melastomataceae, and Poaceae. Borreria sp, Clidemia Hirta, Commelina difusa and Imperata cylindrica was  an important and very dominant weed in all young Eucalyptus spp planting area. Keywords: Inventory, Eucalyptus spp, weeds.